2000
DOI: 10.1039/b004775i
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected valence bond isomerization to the heteroaromatic ring system: [1,2,3]triazolo[4,5-d]pyridazine

Abstract: The arylazo substituted salt 2 when treated with a base underwent a valence bond isomerization to yield a derivative of the heteroaromatic ring system, [1,2,3]triazolo[4,5-d]pyridazine (4). Scheme 1 (a) Ar = 4-ClC 6 H 4 -, (b) Ar = 4-NO 2 C 6 H 4 -, (c) Ar = 4-CH 3 OC 6 H 4 -.Fig. 1 A molecular diagram 9 of 4b with the numbering of atoms. Anisotropic displacement parameters represent 50% probabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Treatment of the arylazopyridazo[1,2,4]triazine tetrafluoroborate 43 with strong bases leads to the formation of the corresponding base, which undergoes a Bolton-Katritzky rearrangement to [1,2,3]triazolo-[4,5-d]pyridazine 44 [35]. …”
Section: Rearrangementsmentioning
confidence: 99%
“…Treatment of the arylazopyridazo[1,2,4]triazine tetrafluoroborate 43 with strong bases leads to the formation of the corresponding base, which undergoes a Bolton-Katritzky rearrangement to [1,2,3]triazolo-[4,5-d]pyridazine 44 [35]. …”
Section: Rearrangementsmentioning
confidence: 99%
“…We have found that dipolar cyclizations, Michael additions and some other interesting transformations due to the zwitterionic character can be realized [5,6]. As a continuation of these studies we have investigated the reactivity of 7 toward aryldiazonium salts [7]. The rapid appearance of a deep red color of the reaction mixture indicated that most possibly an azo coupling took place, and structure analysis of the red crystals (8) isolated from the reaction mixture provided satisfactory support for this assumption.…”
mentioning
confidence: 99%